Metabolic reaction network-based recursive metabolite annotation for untargeted metabolomics - Xiaotao Shen (Nature Portfolio, 2019)
Untargeted metabolomics detects large numbers of metabolites but their annotation remains challenging. Here, the authors develop a metabolic reaction network-based recursive algorithm that expands metabolite annotation by taking advantage of the mass spectral similarity of reaction-paired neighbor metabolites.